2014
DOI: 10.7897/2277-4343.05369
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Some Anthraquinones of Rubia Cordifolia L. Incorporated Into Pinda Oil: An Ayurvedic Medicinal Oil Used for Topical Application in Dermatological and Inflammatory Conditions

Abstract: 'Pinda oil' is an Ayurvedic medicinal oil use in dermatological and inflammatory conditions, prepared from Rubia cordifolia, Glycyrrhiza glabra and Cryptolepis buchnani. Qualitative and quantitative analysis of plant secondary metabolites incorporated in the oil is important in the standardization of the oil. The oil has a deep wine red color due to the incorporation of anthraquinones from Rubia cordifolia. The major anthraquinones present in 'Pinda oil' were identified to be alizarin, xanthopurpurin, purpurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…The treatment showed re-pigmentation in affected white patches and reduced symptoms, suggesting it could be a promising treatment approach (Ediriweera et al, 2009). It has also been reported that an Ayurvedic medicinal oil called "Bakuchi Oil" prepared from the dried fruits of Psoralea corylifolia L. (Fabaceae) which contains furanocoumarin and psoralen is used for the treatment of vitiligo in Sri Lanka (Abeysekera et al, 2012).…”
Section: Product Development By Natural Plant Materialsmentioning
confidence: 99%
“…The treatment showed re-pigmentation in affected white patches and reduced symptoms, suggesting it could be a promising treatment approach (Ediriweera et al, 2009). It has also been reported that an Ayurvedic medicinal oil called "Bakuchi Oil" prepared from the dried fruits of Psoralea corylifolia L. (Fabaceae) which contains furanocoumarin and psoralen is used for the treatment of vitiligo in Sri Lanka (Abeysekera et al, 2012).…”
Section: Product Development By Natural Plant Materialsmentioning
confidence: 99%